Household Income of Beef Cattle Farmer in Manokwari - Herawati, Maria; Anwarudin, Oeng (Jurnal Penyuluhan Pertanian, 2023)
The purpose of this study was to determine the household income of beef cattle farmer in Manokwari Regency. The samples used were 173 beef cattle farmer. Data analysis used quantitative data to determine farmer household income. The results of this study show that the average income of beef cattle farmer from on farm in Manokwari Regency is the largest in cattle ownership of more than 10 tails, followed by 5-10 tails and less than 5 tails. It show that the more the number of livestock so that the higher the income. Beef cattle farmer income in Manokwari Regency comes from on farm, off farm and non farm. Income from on farm has a higher contribution compared to income from off farm and non farm.